2016
DOI: 10.1007/s00170-016-9853-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reinforcement type on the microstructure, mechanical properties, and wear resistance of A356 matrix composites produced by FSP

Abstract: Fabrication of particle-reinforced aluminum matrix composites has been pursued with a keen interest recently. However, a comparison of the effect of different reinforcements on the mechanical properties and wear resistance of A356 matrix composites fabricated by FSP is of great interest to be considered. In the present work, the microstructural, mechanical, and wear properties of A356 matrix composites reinforced by SiC, TiC, ZrO 2 , and B 4 C particles are investigated. Moreover, the effect of pin profile on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 48 publications
(75 reference statements)
0
20
0
Order By: Relevance
“…Typical particle reinforcements are silicon carbide and aluminium oxide, but titanium diboride, boron carbide, titanium aluminide, or titanium dioxide can also be used [1]. The fabrication is realised by casting processes (e.g., stir casting, squeeze casting, in-situ-casting, spray casting, infiltration), powder metallurgy routes, friction stir processing [2], or selective laser melting [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Typical particle reinforcements are silicon carbide and aluminium oxide, but titanium diboride, boron carbide, titanium aluminide, or titanium dioxide can also be used [1]. The fabrication is realised by casting processes (e.g., stir casting, squeeze casting, in-situ-casting, spray casting, infiltration), powder metallurgy routes, friction stir processing [2], or selective laser melting [3].…”
mentioning
confidence: 99%
“…This can be referred to the behaviour of the ceramic particles acting as load-bearing components. Furthermore, the contact area between the AMC part and the counterpart is markedly reduced [2]. However, the surface structure of the friction partners strongly affects the mechanisms of action in tribological systems.…”
mentioning
confidence: 99%
“…It was reported that the volume percentage of doping reinforcement in surface composites fabricated through FSP mainly affected by reinforcing methods and size of groove. It was found that composite fabricated by three gradient grooves reinforcing techniques, experiences better in hardness compared to other techniques [70,71].…”
Section: Reinforcement Strategymentioning
confidence: 96%
“…SiC and Al 2 O 3 are the most commonly used reinforcement particles to fabricate AZ91Mg alloy based surface composites using FSP. B 4 C particles possess lower density, higher hardness, good thermal and chemical stability comparable to SiC and Al 2 O 3 [27,28]. Nanaksharan et al reported the preliminary wear characteristics of B 4 C reinforced AZ91 matrix composite fabricated by FSP [29].…”
Section: Introductionmentioning
confidence: 99%